The practice of faith in everyday life based on the metrical books of various denominations in the period of Galician autonomy (as illustrated by Rzeszów) - Rejman, Sabina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
This article aims to highlight aspects of religious life based on metrical records. The research focuses on religious communities in Rzeszów: the Roman Catholic parish of Farna, the Jewish metrical district, and the Greek Catholic parish in Zalesie. In all of these communities, the choice of wedding dates was in accordance with the liturgical calendar, including holidays and fasting periods. Illegitimate births indicated that relationships typical of marriage were also established before the formal wedding ceremony. Illegitimate births were more common among Jews due to marriages concluded only according to their own ritual. Illegitimate births were also more prevalent in the urban-like Farna parish compared to the rural Greek Catholic parish, where their percentage was the lowest. Records of administering sacraments to the dying were also indicative of religiousness.

Niniejszy artykuł ma na celu ukazanie aspektów życia religijnego w świetle akt metrykalnych. Przedmiotem badań są wspólnoty wyznaniowe w Rzeszowie: rzymskokatolicka parafia Farna, żydowski okręg metrykalny i greckokatolicka parafia w Zalesiu. We wszystkich terminu ślubu wybierano zgodnie z rozkładem świąt i postów w roku liturgicznym. Urodzenia pozamałżeńskie dowodziły, że relacje typowe dla małżeństwa nawiązywano też przed ślubem. Urodzenia pozamałżeńskie zanotowano u Żydów z powodu małżeństw zawieranych tylko rytualnie. Więcej było ich też w parafii Farnej o miejskim charakterze, inaczej w wiejskiej parafii greckokatolickiej, gdzie udział procentowy urodzeń pozamałżeńskich był najniższy. Na religijność wskazywały również zapisy o zaopatrzeniu umierającego sakramentami.
Wiara a praktyka życia codziennego na podstawie ksiąg metrykalnych różnych wyznań w okresie autonomii galicyjskiej (na przykładzie Rzeszowa)
Keywords: Galicia; metrical records; religiosity; Latin Catholics; Greek Catholics; Jews; Galicja; metryki; religijność; łacinnicy; grekokatolicy; Żydzi